Polyphase deformation of the Youjiang fold-and-thrust belt during the Mesozoic: Implications for the tectonic transition of the South China block - Hu, Jia-Xiu; Xiao, Chang-Hao; Wei, Chang-Shan; Shen, Yu-Ke; Chen, Zheng-Le; Zhang, Yu; Zhang, Da (Frontiers in Earth Science, 2023)
The South China block (SCB) experienced the tectonic transition from the Paleo-Tethys to the Paleo-Pacific tectonic domains during the Mesozoic, but the transition process is hotly debated. The Youjiang fold-and-thrust belt (YFTB), in the interior of the Youjiang Basin in the southwestern SCB, is located in a junction of these two tectonic domains and thus witnessed their tectonic evolution. It also separates the northern thin-skinned structures from the southern thick-skinned structures in the basin. Therefore, the YFTB is an intriguing window into the Mesozoic evolution in the southwestern SCB and the Mesozoic tectonic transition of the SCB. In this study, we conduct structural analysis at the middle of the YFTB and discuss the Mesozoic tectonic transition of the SCB. Four phases of deformation are identified in the YFTB during the Mesozoic. The first phase of deformation (D1) is characterized by a series of conjugate joints, NW–SE trending thrust faults and folds resulting from NE–SW shortening that was related to the collision between the SCB and Indochina block. The second phase of deformation (D2) is manifested by the pre-existing NW–SE striking thrust faults transformed to normal faults and the Late Triassic mafic magmatism. Our structural observations, combined with previous geochronological data for mafic dykes, suggest the study area experienced post-orogenic extension in the Late Triassic. The third phase of deformation (D3), accompanied with the westward subduction of the Paleo-Pacific oceanic plate, is represented by a series of conjugate joints and NE–SW-striking faults formed by NW–SE compression. As a result of the continuous subduction of the Paleo-Pacific plate and its subsequent slab rollback, the fourth phase of deformation (D4) is featured with normal faults, magmatic-hydrothermal activities, and regional mineralization, which are associated with the nearly E–W extension setting. Our study results indicate that, in the Early Mesozoic, the Youjiang Basin was dominated by the Paleo-Tethys domain and then transitioned to the Paleo-Pacific domain. Together with the magmatic lull between the Triassic and the Early-Middle Jurassic identified in the SCB, we propose that the tectonic transition process manifested in the YFTB more likely initiated in the Early Jurassic.